Dry Сough in Сhildren: Сauses, Peculiarities of Respiratory Diseases and Treatment - Yu.V. Marushko; O.D. Moscovenko (Zaslavsky O.Yu., 2016)
Dry cough is one of the first symptoms of many respiratory diseases in children. Some diseases of other organs and systems also can be associated with dry cough. In any case the choice of expectorants or antitussive drugs depends on the diagnosis and peculiarities of cough at this disease. Herbal medical products are effective and safe for cough treatment.